SISTEM PENGENDALIAN SUHU AIR PADA PROSES INKUBASI YOGHURT BERBASIS MIKROKONTROLER ARDUINO UNO - Muhammad Rafif Rasendriya Sandhie; n/a Nurussa’adah; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
Yogurt is a food product that is widely consumed. The manufacturing process is by mixing the Lactobacillus bulgaricus and Streptococcus thermophilus bacteria into milk and proceed with the incubation stage. In the incubation process, the temperature of the milk must be carefully maintained with a normal time of around 16 hours in order to produce a good product. This makes yogurt producers quite difficult because they still use manual methods. Therefore, a water temperature control tool was made in this yogurt incubation process. This tool works by placing milk that has been treated with bacteria in a container surrounded by water. The water temperature will be maintained so that the temperature of the yogurt is maintained. Temperature control is carried out using the PI control method to make it easier for yogurt producers to carry out the production process. The ziegler-nichols method is used to obtain Kp and Ki parameters. Based on the test results, the PI control can control the water temperature well with the parameters Kp = 49.87 and Ki = 0.033. The response of the testing system for controlling water temperature in the yogurt incubation process with a yoghurt temperature setpoint of 45°C obtained that the water temperature reached steady state at 12771 seconds with an overshoot of 4.8% and a steady state error of 1.6%. For the yogurt temperature value to reach steady state occurs in the 6594th second with a steady state error of 4.1%. In the yogurt incubation process which lasted for ± 10 hours, it was found that the temperature difference between the water and yogurt was an average of 1.63°C. Keywords: yogurt, temperature, PI control, ziegler-nichols